Chemotherapy in hodgkin's disease (lymphadenoma). Issue 15 (20th July 1973) - Unknown
Abstract : The extent of Hodgkin's disease at the time of diagnosis is the most important single factor affecting prognosis and the choice of treatment. 1 2 Thorough investigation is needed to determine the stage of the disease, 3 and it is best to refer patients to a centre with special experience of the condition. The staging process requires haematological, biochemical and radiographic studies, including abdominal lymphography. 4 Some patients may also need laparotomy with splenectomy and hepatic and node biopsy to localise any intra-abdominal spread, particularly into the liver which is ominous and an important determinant in the choice of therapy. 5 6 Laparotomy is less usually performed in patients over 60. In children under 6 splenectomy should not be carried out because it makes them more susceptible to infection. 7 In young women the ovaries may be sewn to the abdominal wall in the mid-line so that they can be shielded from x-rays directed at iliac lymph nodes.